Current laboratory diagnostics of coronavirus disease 2019 (COVID-19) - Lippi, Giuseppe; Mattiuzzi, Camilla; Bovo, Chiara; Plebani, Mario (Acta Biomedica Atenei Parmensis, 2020)
Laboratory medicine provides an almost irreplaceable contribution to the diagnostic reasoning and managed care of most human pathologies. The novel coronavirus disease 2019 (COVID-19) is not an exception to this paradigm. Although the relatively recent emergence does not allow to draw definitive conclusions on severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) diagnostics, some standpoints can be conveyed. First and foremost, it seems now clear that we will be living together with this virus for quite a long time, so that our vigilance and responsiveness against the emergence of new local outbreaks shall be maintained at the highest possible levels. The etiological diagnosis of COVID-19 is, and will remain for the foreseeable future, deeply based on direct identification of viral RNA by means of molecular biology techniques in biological materials, especially upper and lower respiratory tract specimens. Whether other materials, such as blood, urine, stools, saliva and throat washing, will become valid alternatives has not been unequivocally defined so far. As concerns serological testing, promising information can be garnered from preliminary investigations, showing that the vast majority of COVID-19 patients seem to develop a sustained immune response against the virus, characterized especially by emergence of anti-SARS-CoV-2 IgG and IgA, 1 to 2 weeks after the onset of fever and/or respiratory symptoms. Whether these antibodies will have persistent neutralizing activity against the virus is still to be elucidated on individual and general basis. The availability of rapid tests for detecting either viral antigens or anti-SARS-CoV-2 antibodies are a potentially viable opportunity for purposes of epidemiologic surveillance, though more information is needed on accuracy and reliability of these portable immunoassays.